Preparation of Some Benzothiazole Polymers and Study Their Electrical Conductivity Properties - Asaad Khattab; Haitham Ayoob; Laith Altaan (College of Education for Pure Sciences, 2020)
As the conjugated polymers are doped with some electron donor or acceptor dopants, their electrical conductivity increased thoroughly to about 10-6 Ω-1.cm-1. The doping of the polymers may give an n or p semiconductor characteristic according to the types of the dopants that are used. Within the frame of this work, four types of conjugated polymers with benzothiazole as a major moiety in their backbone have been prepared. The prepared monomers and polymers have been characterized by FTIR spectroscopy. Elemental analysis of the polymers (CHN) demonstrates their chemical structure while the DSC thermal analysis illustrates its Tg. The polymers were doped with two types of dopants, iodine and sodium iodide. The electrical conductivity of the doped polymers was measured with three probe cell. The results show increasing in the electrical conductivity with dopant concentration to some levels. The activation energy of the electrical conductivity process was also studied by measuring the electrical conductivity in different temperature. According to the magnitude of the activation energy, we can conclude that the chain flexibility is the dominate factor that influenced on electrical conductivity. Hall Effect and hot probe measurements reveal that the polymer can be considered as n or p type according to the type of the doping. It was concluded that the doping with iodine produced an n-type while the doping with sodium iodide produced the p- type.